2008
DOI: 10.1080/10255840701492118
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional cerebrospinal fluid flow within the human ventricular system

Abstract: Cerebrospinal fluid (CSF) is a Newtonian fluid and can, therefore, be modelled using computational fluid dynamics (CFD). Previous modelling of the CSF has been limited to simplified geometric models. This work describes a geometrically accurate three dimensional (3D) computational model of the human ventricular system (HVS) constructed from magnetic resonance images (MRI) of the human brain. It is an accurate and full representation of the HVS and includes appropriately positioned CSF production and drainage l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…However, previous studies have suggested that these effects are small in CSF. 16 To determine whether these effects are important, future work will compare these results with a CFA method in which inertial effects are included; additional validation could be achieved with PCMR imaging at multiple levels or with a 3D PCMR technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies have suggested that these effects are small in CSF. 16 To determine whether these effects are important, future work will compare these results with a CFA method in which inertial effects are included; additional validation could be achieved with PCMR imaging at multiple levels or with a 3D PCMR technique.…”
Section: Discussionmentioning
confidence: 99%
“…14 CFA studies of the ventricular system have been performed, 15,16 but these are not relevant to the Chiari I malformation. Some physical models have been created; an in vitro study of syringomyelia hydrodynamics was performed with a phantom model of the spinal canal created from MR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The high ICP compresses the ON at its junction with the globe and distends its prelaminar axons as their axoplasm piles up at the scleral lamina. 22 Howden et al 26 found that CSF velocity is substantially slower in areas farther away from its inlets and that at certain sites, the flow nearly stagnates. Therefore, any reduction in CSF flow rate should first affect the SAS of the ON, which is farther away from the ventricles and anatomically does not allow continuous flow.…”
Section: Pathogenesis Of Papilledemamentioning
confidence: 99%
“…Therefore, any reduction in CSF flow rate should first affect the SAS of the ON, which is farther away from the ventricles and anatomically does not allow continuous flow. 26 The ischemic theory postulates that elevated ICP causes reduced perfusion of the ON axons. The retrolaminar region of the ON is a watershed area and is prone to ischemic insult.…”
Section: Pathogenesis Of Papilledemamentioning
confidence: 99%
“…These are known to produce pulsatile CSF flow with velocities several orders of magnitude larger than those generated by the cilia [15][16][17][18][19][20]. Vice versa, none of the investigations of large-scale CSF dynamics has taken into account the effect of cilia motion.…”
Section: Introductionmentioning
confidence: 99%